Personhood and a meaningful life in African philosophy - Molefe, Motsamai (South African journal of philosophy, 2020)
This article proffers a personhood-based conception of a meaningful life. I look into the ethical structure of the salient idea of personhood in African philosophy to develop an account of a meaningful life. In my view, the ethics of personhood is constituted by three components, namely (1) the fact of being human, which informs (2) a view of moral status qua the capacity for moral virtue, and (3) which specifies the final good of achieving or developing a morally virtuous character. In light of the ethics of personhood, I will propose the view that a meaningful life is a function of achieving moral excellence or perfection. The moral perfection proposed here, to embody a meaningful life, is of a deontological and satisficing kind. The achievement of satisfactory levels of moral excellence, within sociopolitical and moral limits, captures the essence of a meaningful life. I conclude the article by considering objections against the view proposed here.